2018
DOI: 10.15252/emmm.201708587
|View full text |Cite
|
Sign up to set email alerts
|

Reinstating plasticity and memory in a tauopathy mouse model with an acetyltransferase activator

Abstract: Chromatin acetylation, a critical regulator of synaptic plasticity and memory processes, is thought to be altered in neurodegenerative diseases. Here, we demonstrate that spatial memory and plasticity (LTD, dendritic spine formation) deficits can be restored in a mouse model of tauopathy following treatment with CSP‐TTK21, a small‐molecule activator of CBP/p300 histone acetyltransferases (HAT). At the transcriptional level, CSP‐TTK21 re‐established half of the hippocampal transcriptome in learning mice, likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 86 publications
6
55
0
Order By: Relevance
“…Our RNA-Seq results from the WT group comparison (learning versus homecage) supports the present literature that learning induces CREB and CREM target genes that both interact with CBP for its transactivation (12,78,79). Among the CREB downstream genes, we found several activity-dependent genes (such as Arc, Egr1, Fos, Nr4a1, JunB) that previously have been shown upregulated following hippocampus-dependent learning (31,80,81). It is noteworthy that some of these activity-dependent genes were downregulated in CBP KIX/KIX mice, including Nr4a1.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our RNA-Seq results from the WT group comparison (learning versus homecage) supports the present literature that learning induces CREB and CREM target genes that both interact with CBP for its transactivation (12,78,79). Among the CREB downstream genes, we found several activity-dependent genes (such as Arc, Egr1, Fos, Nr4a1, JunB) that previously have been shown upregulated following hippocampus-dependent learning (31,80,81). It is noteworthy that some of these activity-dependent genes were downregulated in CBP KIX/KIX mice, including Nr4a1.…”
Section: Discussionmentioning
confidence: 60%
“…Reducing Nr4A function in the hippocampus impairs long-term memory (82)(83)(84), while the activation of Nr4A family transcription factors enhances memory in young (85) and aged mice (86,87). Pharmacological activation of CBP in a mouse model of Alzheimer's disease rescues Nr4A gene expression and long-term memory (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that p300-mediated acetylation of beclin 1, VPS34, and SIK2 inhibits autophagy initiation, autophagosome maturation, and endocytic trafficking [34,52,53], suggesting that these proteins may play a role in regulating secretion of tau and potentially other proteins. Secondly, as p300/CBP regulates histone acetylation, the mechanism could also involve epigenetic changes in the autophagyrelevant transcriptome and synaptic plasticity [21,54,55]. Finally, acetylation of tau itself by p300/CBP increases tau toxicity, which could lead to cell damage such as impaired cytoskeleton stability and membrane integrity, and in turn contribute to elevated secretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be determined whether p300/CBP affects posttranslational modification of transmitted tau species, or tau seed uptake. In addition, p300/CBP's other effects on neurons [21], including neuronal plasticity [55,67] could also indirectly contribute to modulation of tau spreading. Finally, glial cells may contribute to tau spreading [68], and the p300/CBP-autophagy pathway could also be involved in these cells.…”
Section: Discussionmentioning
confidence: 99%